P071 Actigraphy-Derived Rest-Activity Rhythms Predict Sleep-Related Self-Report Outcomes in Women Receiving Chemotherapy for Breast Cancer. (9th November 2022) - Maccora, J; Bean, H; Phillips, A; Diggens, J; Ftanou, M; Alexander, M; Stafford, L; Francis, P; Bei, B; Wiley, J
Abstract: Introduction: Circadian rest-activity rhythms (RARs) disruption is common during chemotherapy for breast cancer, but little is known regarding its association with sleep and daytime functioning. In this study, we evaluated whether objectively-assessed RARs prospectively predict self-reported insomnia and fatigue symptoms, daytime sleep-related impairment, and sleep disturbance. Methods: This is a secondary analysis of a trial. Participants (N=101) were randomized to cognitive behavioural plus light therapy or relaxation audios. Participants wore an actigraph continuously throughout the 6-week intervention. RAR indices (interdaily stability, intradaily variability, relative amplitude, least active 5h period [L5], most active 10h period [M10]) were calculated based on two weeks (4 & 5). Self-reported outcomes were assessed at weeks 3 and 6. Self-reported outcomes at week 6 were predicted by RAR indices controlling for self-reported outcomes at week 3 and intervention condition. Results: Lower L5 predicted lower self-reported insomnia and fatigue symptoms, sleep-related impairment, and sleep disturbance (all p<.05). With the exception of insomnia symptoms (p>.05), higher inter-daily stability predicted lower symptoms of fatigue, sleep-related impairment and sleep disturbance (all p<.05). Similarly, excluding sleep disturbance (p>.05), higher relative amplitude predicted fewer endorsed symptoms on self-reported measures (all p<.01). Neither M10 nor intradaily variability predicted self-reported outcomes (all p>.05). Discussion: RAR disruption demonstrated the most reliable association with daytime sleep-related complaints. The entrainment of a robust diurnal rhythm may reflect a novel intervention target. Direct intervention on distinct RAR characteristics may yield secondary gains on several self-reported sleep-related outcomes, particularly those related to daytime functioning. Trial Registration: ACTRN12618001255279